KOMPETENSI SUMBER DAYA APARATUR DI KECAMATAN PRAMBANAN KABUPATEN SLEMAN - Eka Novian Gunawan; Eko Budi Santoso; Galang Krisna Aji Pratama (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This paper aims to describe the competency of civil servants in Kecamatan Prambanan Kabupaten Sleman. Using interview and observation as a research method, the result is described using the frameworks of the definition of competency in Law Number Number 5 of 2004 on Civil Servant Apparatus. The results show that there are problems in technical competency and managerial competency such as lack of skill of personnel due to small chances for workers to get training and almost half of the workers have not to reach higher education. Key words: competency; education; traning; district.